Quantifying water movement in soils irrigated by continuous drip irrigation with citrus in the Western Cape - Van der Merwe, Johan Herbst (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.